Persistence Reflected In Dan Brown's The Da Vinci Code Novel (2003): A Psychoanalytic Approach - Ayu Mastuti, Siwi; , Titis Setyabudi,S.S. M.Hum (2017)
The main issue of this research is persistence. Everyone has persistence to reach or reveal something. The purpose of this research paper is to analyze persistence reflected in Dan Brown's The Da Vinci Code novel especially on the main character of the novel, Robert Langdon based on psychological approach. The researcher used qualitative method. The researcher used two data sources: primer and secondary. The primer data was The Da Vinci Code novel by Dan Brown. The sources of secondary data are taken from other sources related the study, such as: website, dictionary, and some books which support the research. For data analysis, the researcher used descriptive qualitative research. Based on analysis, the researcher took some conclusions. This study that to reveal some problems must with persistence, so there is no misunderstanding. Robert Langdon helped by Sophie reveal Sauniere's decease with his persistence. Keyword: persistence, The Da Vinci Code, Dan Brown, psychoanalytic.